Implementasi olah data tekanan udara ekstrim dari BMKG untuk meningkatkan hasil belajar siswa pada pokok bahasan tekanan Di SMP Negeri 4 kota Bengkulu - Ria Agustin; Muhammad Farid; Nirwana Nirwana (University of Bengkulu, 2019)
AbstraCT[Implementation of Extreme Air Pressure Data Processing from BMKG to Improve Students Learning Outcomes on the Subject of Pressure in SMPN 4 Bengkulu City]. This Study aims to ;1) produce pressure simulations in the form of images as teaching materials on the concept of air pressure; 2) produce teaching materials in grapichal form so that they. This research is a quasi-experimental research based on purposive sampling technuque with the nonequivalent control group design. The sample in this study amounted to two classes, namely VIII.1 as a control class and VIII.2 as an experimental class with a total sample of 30 students in each class. the instrumen in thus study was in the form of objective testa of 10 questions with four answer choices. The results of the study show: 1) air pressure is influenced by temperature, altitude of place and the distribution of oceans and land. Highest air pressure of 1013,8 milibar, lowest air pressure of 1004,0 milibar and the average air pressure of 1008,6 milibar; 2) there are differences in learning outcomes between students taught with instructional materials of extreme air pressure data from BMKG with inquiry models with students taught with a discussion and assignment model shown by thitung > ttabel ( 7,63 > 2,01) with a significance level 5 %. Keywords: Air pressure; temperature; height; Inquiry. (Received July 27, 2019; Accepted September 18, 2019; Published October 24, 2019) AbstrakPenelitian ini bertujuan untuk:1) mendeskripsikan tekanan udara tertinggi, terendah dan tekanan udara rata-rata, 2) mengetahui perbedaan hasil belajar kognitif siswa antara antara siswa yang diajar menggunakan olah data tekanan udara ekstrim dari BMKG dengan model inkuiri terhadap siswa yang diajarkan menggunakan model diskusi dan penugasan. Penelitian ini adalah penelitian eksperimen semu berdasarkan teknik Purposive Sampling dengan desain nonequivalent control group design. Sampel yang digunakan dalam penelitian ini berjumlah 2 kelas yaitu kelas VIII.1 sebagai kelas Kontrol dan kelas VIII.2 sebagai kelas ekeperimen dengan jumlah sampel dalam tiap kelas sebanyak 30 orang siswa. Instrumen yang digunakan dalam penelitian ini berupa tes objektif sebanyak 10 soal dengan empat pilihan jawaban. Hasil penelitian menunjukkan: 1) Tekanan udara dipengaruhi oleh temperature, ketinggian suatu tempat, serta sebaran lautan dan daratan. Tekanan udara tertinggi sebesar 1013,8 milibar, terendah 1004,0 milibar dan rata-rata tekanan udara sebesar 1008,6 milibar; 2) terdapat perbedaan hasil belajar kognitif antara siswa yang diajar menggunakan bahan ajar berupa olah data tekanan udara ekstrim BMKG dengan model inkuiri dengan siswa yang diajar dengan model pembelajaran diskusi dan penugasan yang ditunjukkan dengan thitung > ttabel ( 7,63 > 2,01)dengan taraf signifikasi 5%.Kata kunci: Tekanan udara; temperatur; ketinggian; model Inkuiri.